Hemodynamic instability and retinal vein occlusion in glaucoma: Comparative analysis of heart rate variability and choroidal perfusion - Ji Hye Lee; Young-Hoon Park (PLoS ONE, 2026)
Purpose To assess the hemodynamic and structural differences between glaucoma patients who developed retinal vein occlusion (RVO) and those who did not. Study design Retrospective, single-center, case-control study Methods This study included glaucoma patients who underwent a heart rate variability (HRV) test between January 2018 and July 2024. Patients were subdivided into RVO and non-RVO groups. Baseline mean deviation (MD) and pattern deviation (PSD) of the visual field and optical coherence tomography parameters were analyzed. Results Twenty-nine glaucoma patients with RVO and 34 glaucoma patients without RVO were included. Baseline MD and PSD had no difference (MD: −5.98 ± 9.05 vs. −3.70 ± 4.70, p = 0.114; PSD: 3.88 ± 3.78 vs. 3.98 ± 3.96, p = 0.883). HRV parameters, specifically Standard Deviation of NN interval (SDNN) and root-mean-square of successive differences (rMSSD), were significantly lower in the RVO group (SDNN: 22.12 ± 8.27 vs. 36.71 ± 24.74, p = 0.002; rMSSD: 16.34 ± 9.55 vs. 29.87 ± 31.58, p = 0.022). A significant difference in choroidal vascularity index was also observed between groups (64.62 ± 7.38 vs. 67.49 ± 5.90, p = 0.045). In a parsimonious multivariable logistic regression model, no variable retained statistical significance. Conclusion This study suggests that reduced heart rate variability, reflecting autonomic dysfunction, is associated with the development of RVO in glaucoma patients. Although these associations did not remain statistically significant in multivariable analysis, the consistent univariate findings indicate that HRV may serve as a potential vulnerability marker rather than an independent predictor. Further prospective studies are warranted to clarify the clinical utility of HRV in risk stratification for RVO in glaucoma patients.